2021
DOI: 10.1007/978-3-030-65396-5_96
|View full text |Cite|
|
Sign up to set email alerts
|

Compaction of Aluminium Foil and Its Effect on Oxidation and Recycling Yield

Abstract: One of the problems when recycling aluminium is its oxidation and consequent metal loss. This is especially critical for the thin sheet/foil materials used for food packaging applications. Compacting the scrap into briquettes may partly reduce such losses in addition to facilitate transport and storage. Shredded aluminium materials of different thicknesses (15-300 µm) were compacted into cylindrical briquettes of 4 cm diameter, each weighting 20 g by uniaxial pressure or moderate-pressuretorsion. A sub-set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The rate of reaction varies based on several factors, including oxygen availability and atmosphere, but oxidation increases substantially at temperatures above 700 • C [13]. When melting scrap, especially if it has a large specific area, large metal losses occur due to rapid oxidation, resulting in dross formation that floats towards the surface of the metal [14]. The efficiency of the process is reduced as a result.…”
Section: Protection From Oxidationmentioning
confidence: 99%
“…The rate of reaction varies based on several factors, including oxygen availability and atmosphere, but oxidation increases substantially at temperatures above 700 • C [13]. When melting scrap, especially if it has a large specific area, large metal losses occur due to rapid oxidation, resulting in dross formation that floats towards the surface of the metal [14]. The efficiency of the process is reduced as a result.…”
Section: Protection From Oxidationmentioning
confidence: 99%
“…Compacting the scrap into bales or briquettes is another standard recycling pre-treatment, since it facilitates storage and transport. A previous study [4] showed that compaction could reduce the oxidation of thin scrap, which has a high specific surface area. The correlation between scrap thickness and re-melting losses was previously described by Rossel [5].…”
Section: Introductionmentioning
confidence: 98%
“…Research has also shown that compacting clean, dry aluminium swarf [27,28] into briquettes increases its recycling efficiency in a salt-free process. Furthermore, briquetting thin aluminium foil can prevent high-temperature-oxidation and the consequent entrapment of small beads by the salt residues [29]. The benefits of compaction could be explained by, depending on the process, the reduction of the surface area exposed to oxidation, the higher density allowing the scrap to sink into the melt, or the enhanced metal-metal contact.…”
Section: Introductionmentioning
confidence: 99%